PENGARUH PEMBERIAN PAKAN KOMPLIT MENGANDUNG BERBAGAI LEVEL TONGKOL JAGUNG TERHADAP PENAMPILAN KAMBING JANTAN - Mide, Muhammad Zain (Teknosains: Media Informasi Sains dan Teknologi, 2017)
Corn cobs is one of agriculture waste which is applicable as one of alternative feed ingredients, despite its low nutritional and high fibre contents; it can used as fibre resource of complete feed to male goats. The objective of this research is to evaluate effects of giving total mixed ration containing different levels of corn cobs on performance male goats. The experiment was carried out according to 4 x 4 Latin Square Design. In each period of 12 days, each goat was randomly assigned to one of the following treatments: T1 (complete ration containing 30 % corn cobs), T2 (complete ration containing 35 % corn cobs), T3 (complete ration containing 40 % corn cobs), and T4 (complete ration containing 45 % corn cobs). The result of the study is the treatments did not indicate a tangible effect (P>0, 05) to the performance of male goats. In conclusion, different levels of corn cobs in complete feed did not negatively affect the performance of male goats.